A culture of compassion: How timeless principles of kindness and empathy become powerful tools for confronting today's most pressing healthcare challenges. Issue 3 (May 2019) - Cochrane, Bonnie S.; Ritchie, Debbie; Lockhard, Daniela; Picciano, Gino; King, John A.; Nelson, Brian
The role of compassion in healthcare is receiving increased attention as emerging research demonstrates how compassionate patient care can improve health outcomes and reduce workplace stress and burnout. To date, proposals to encourage empathy, kindness, and compassion in healthcare have focused primarily on training individual care providers. This article argues that increasing the awareness and skills of individuals is necessary but insufficient. Compassionate care becomes an organizational norm only when health leaders create and nurture a "culture of compassion" that actively supports, develops, and recognizes the role of compassion in day-to-day management and practice. The article profiles four organizations that have adopted compassionate healthcare as an explicit organizational priority and implemented practical measures for building and sustaining a culture of compassion. Common principles and practices are identified. These organizations demonstrate how compassion can lead directly to improved outcomes of primary importance to healthcare organizations, including quality and safety, patient experience, employee and physician engagement, and financial performance. They show how compassion can be a powerful yet often underappreciated tool for helping organizations successfully manage current challenges.